[PP.30.07] DIURNAL PATTERN OF URINARY SODIUM/POTASSIUM RATIO IN FREE LIVING JAPANESE IN DIVIDUALS. (September 2016) - Iwahori, T.; Ueshima, H.; Torii, S.; Saito, Y.; Kondo, K.; Miyagawa, N.; Arima, H.; Miura, K.
Abstract : Objective: High dietary sodium (Na), low dietary potassium (K) intakes and high Na/K ratio are associated with adverse blood pressure levels and excess risks of cardiovascular diseases. Handy urinary Na/K ratio measurement device provides feedback in several ten seconds with far lower patient burden as compared to conventional methods. Since there is no report on diurnal variation of casual urinary Na/K ratio, we clarified it under free living conditions in Japanese participants. Figure. No caption available. Design and method: This study is a cross sectional study. A total of 122 normotensve and hypertensive individuals (ages 25–69 years) were recruited. Participants were instructed to collect all casual urine samples in aliquot tubes (10 mL), and to report urine volume and the time at each voiding under free living conditions for 10 to 22 days. Urinary sodium and potassium concentration was measured by ion-specific electrodes, and Na/K ratio was calculated. 13, 277 specimens were collected and classified into hourly data from 00:00 hours to 23:00 hours on the hour. Diurnal pattern of urinary Na/K ratio, urinary concentrations and excretions of sodium and potassium, and urine volume were evaluated. Results: Mean value of 24-hr urinary Na/K ratio were 4.37 and 3.43 in normotensive and hypertensive individuals, respectively. Of the individuals on anti-hypertensive medications, 14 participants, 9 participants, 15 participants and 5 participants were taking calcium channel blockers (CCB), angiotensin 2 receptor blockers (ARB), both CCB and ARB, and other drugs, respectively. Overall mean value of urinary Na/K ratio was highest (4.1–5.0) in the early morning, lower (3.3–3.8) in daytime and higher (4.0–4.4) toward evening hours. Mean urinary sodium and potassium concentration was lowest (90–110mmol/L, 24–32mmol/L, respectively) in the early morning, and higher (110–140mmol/L, 35–43mmol/L, respectively) after second voiding. Diurnal variability ratio of potassium concentration was larger than sodium concentration. In subgroup analysis, diurnal patterns of mean urinary Na/K ratio were comparable between normotensive and hypertensive individuals. Conclusions: We identified a diurnal pattern in urinary Na/K ratio under free living conditions. This fluctuation of urinary Na/K ratio was 1 to 1.5, and its variation is not likely to be explained by postprandial surges.